Os hábitos de compras de tutores de pets em Manaus - Moraes, Gabriel Bernardo (Brasil, 2024)
The market presents prosperous results year after year, according to its growth, the market's consumer behavior is shaped by the trends presented by the major players in the sector. The domestication of animals ends up influencing people's social behavior, I have in mind that, at a time prior to the basic function and the service in its exclusivity for guarding functions, therefore, animals reach a path parallel to the home, becoming -You too feels encouraged by esteem. Therefore, it is of great importance to understand this market and the factors that surround it. This is the present work as a quantitative and qualitative research study methodology, carried out through questionnaires applied in the Google Forms tool. The main objective of this research was to analyze the socioeconomic profile and consumer behavior of the pet market in Manaus. The specific objectives are to understand the growing population of Pets in Brazil, investigate the level of attention to consumer expectations in relation to services and products in the pet market in Manaus and identify the most important factors for the consumer in the selection of products and services in this market. . From this study it was possible to understand consumer behavior and the level of satisfaction related to the Pet market in Manaus. The national pet market presents a promising scenario that offers significant opportunities for growth and innovation. Following the prosperous results is the pet market in Manaus, which has presented positive numbers for less than two years.